SELF-HEALING AS A SOLUTION TO OVERCOME STRESS IN FINAL SEMESTER PHYSICAL EDUCATION STUDENTS AT UNIVERSITY - Hidayah, Putri; Apriliyanto, Rizki; Sulaiman, Ahmad (Gladi : Jurnal Ilmu Keolahragaan, 2025)
This study aimed to determine the effect of self-healing on the stress level of final students of sports education education at Muhammadiyah University of Jember. Self-healing is a process of treatment or healing that is carried out based on self-confidence and is also supported by the environment and also external factors. This study uses a quantitative method using a questionnaire instrument with a target of 20 participants from the sports education study program at Muhammadiyah University in Jember. The finding of this article is that the effect of self-healing is proven to be able to minimize stress levels when working on which students are often easily emotional, anxious, overthinking, and even difficult to digest material, therefore with self-healing students can be helped to reduce their burden of thought when working on a thesis.